(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The article focuses on the role of pedagogical technologies in the formation of students’ scientific worldview and its specific features. The problem of pedagogical technologies is studied in depth on a scientific basis from a pedagogical point of view. However, when they are applied to the educational process, it is noted that the issue of psychological impact on the student’s personality (his mental processes) has not been seriously studied so far. After all, the human personality is a psychological object with a very complex and multi-layered structure. Pedagogical technologies affect the student’s personality as a whole, creating certain changes in it. Pedagogical technologies as a way of conveying certain content to the minds of students influence the formation of their scientific worldview. Also, the harmony of form and content of educational tasks, that is, the placement of content on the basis of effective pedagogical technologies, is the basis for the development of students’ scientific outlook. Proof of this is reflected in the article.